"It goes beyond good camaraderie": A qualitative study of the process of becoming an interprofessional healthcare "teamlet". Issue 3 (3rd May 2016) - Harrod, Molly; Weston, Lauren E.; Robinson, Claire; Tremblay, Adam; Greenstone, Clinton L.; Forman, Jane
ABSTRACT: Within the US, the patient-centred medical home has become a predominant model in the delivery of primary care. This model requires a shift from the physician-centric model to an interprofessional team-based approach. Thus, healthcare staff are being reorganized into teams, resulting in having to work and relate to one another in new ways. In 2010, the Veterans Health Administration implemented the patient aligned care team (PACT) model, its version of the patient-centred medical home. The transition to the PACT model involved restructuring primary care staff into "teamlets", consisting of a registered nurse, licensed practical nurse, and administrative clerk for each full-time-equivalent primary care provider. This qualitative study used observation and semi-structured interviews to understand the factors that affect teamlet functioning as they implement this new model of care and how teams are interacting to address those factors. Findings suggest that role understanding includes understanding how each teamlet member's tasks are performed in the daily operations of the clinic. In addition, willingness to perform tasks that benefit the teamlet and acceptance of delegation from all teamlet members were found to be important for teamlet functioning and cohesion. In order for healthcare teams to provide patient-centred care, it is important to provide guidance and support about what these new relationships and roles will entail. The building of team relationships is not a static process; ways of working together build over time and, therefore, should be seen as a continuous cycle of quality improvement.